The role of bioactive lipids in pain and inflammation - Wong, Amy (2012)
Bioactive lipids or lipids that activate specific signalling pathways are involved in the regulation and maintenance of normal bodily functions. Furthermore, bioactive lipid targets have been implicated in a number of conditions such as cancer, asthma and arthritis, all of which contain an inflammatory element. Additionally, a number of bioactive lipids are also known to target several different types of receptors. These include the cannabinoid receptors, peroxisome proliferator activated receptor alpha (PPARα) and transient receptor potential vanilloid-1 (TRPV1) ion channels. The assessment of bioactive lipid levels in biological systems is important for understanding their role in cell function and pathological events.